Qualitative Analysis of Food Products - Varzakas, Theodoros (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Qualitative control and analysis of food products is a requirement for food industries, both in terms of quality assurance and food safety management systems. Analysis of foods is continuously requiring the development of more robust, efficient, sensitive, and cost-effective analytical methodologies to guarantee the safety, quality, authenticity, and traceability of foods in compliance with legislation and consumers' demands.Different analyses include microbiological and chemical analyses, from simple to complex, from old to modern technologies. Hence, fundamental and/or state-of-the-art methods of the development, optimization, and practical implementation in routine laboratories, and validation of these methods for the monitoring of food safety and quality, are employed. Methodologies for food microbial contaminants, food chemistry and toxicology, food quality, food authenticity, and food traceability have been presented and discussed in this Special Issue.